Uji Aktivitas Infusa Rimpang Temu Mangga (Curcuma mangga Valeton and Zijp) sebagai Anti Inflamasi: Anti Inflammation Activity of Temu Mangga (Curcuma mangga Valeton and Zijp) Rhizome’s Infusion - Dyan Fitri Nugraha; Meida Rizki Putri; Helda Melati (Jurnal Surya Medika (JSM), 2022)
Non-Steroid Anti-Inflammatory Drugs (NSAIDs) are drugs that are often used by the public, either to relieve pain or swelling. The use of NSAIDs without proper references followed by high consumption intensity often shows side effects that arise, such as stomach pain, or more fatal results, such as gastric bleeding, chronic kidney disorders, to cardiovascular diseases. Not relying on synthetic drugs, empirically, people consume boiled water from the temu mangga rhizome to treat the inflammation or swelling they experience. The purpose of this study was to scientifically prove the anti-inflammatory activity of the temu mangga rhizome’s infusion, with macroscopic parameters such as edema volume and microscopic anti-inflammatory activity observed from plasma membrane stabilization. The research method was experimental by dividing the preparation into three doses, namely 90 mg, 180 mg, and 360 mg per 200 grams of body weight of test animals in the form of male rats (Rattus norvegicus). The results showed that the test animals' dose of 360 mg/200 gram body weight had the best effectiveness.